KOMUNIKASI PEMERINTAHAN DALAM MENYEBARKAN INFORMASI PUBLIK PADA DISKOMINFO KOTA BUKITTINGGI MELALUI WEBSITE - M.Djorghi Adi Nugraha; Razie Razak (Indonesian Journal of Digital Public Relations (IJDPR), 2022)
Government communication is a process of conveying messages and information carried out by the government to public to obtain government goals and functions. The purpose of this study is to determine the implementation of the dissemination and management of information to the public, which the Bukittinggi City Diskominfo carries out through the website. This research uses qualitative research methods using case study techniques. The data collection carried out in this study is by conducting an interview, observation, and documentation. Based on the research results, the Bukittinggi City Diskominfo uses mass communication to carry out the process of conveying various information to the public. Information related to profile, government, tourism, news, press releases, announcements, and (IPKD). From various information, the news is information that is prioritized to be conveyed to the public. The information submitted is related to the programs and activities of the leadership. The news published by diskominfo Kota Bukittinggi has the meaning of a media agenda. In addition to deliberately creating information, the Bukittinggi City Diskominfo selects information (gatekeeper) that will be published through the website bukittinggikota.go.id. Keywords: Gatekeeper,government communication,management public information,mass communication,media agenda